1997
DOI: 10.1207/s15327558ijbm0404_8
|View full text |Cite
|
Sign up to set email alerts
|

A behavioral treatment of young migrainous and nonmigrainous headache patients: Prediction of treatment success

Abstract: We evaluated the outcome of a behavioral treatment package in a clinical setting with a group of young (age: 12-22) headache patients, suffering from migrainous or nonmigrainous. Comparison between the experimental (n = 24) and the waiting-list control group (n = 15) showed a treatment effect on headache frequency and on the headache index. Using a 50% reduction in the headache activity as a criterion for clinical improvement, 52% of the participants in the experimental group had improved clinically at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
1
18
1
2
Order By: Relevance
“…The full-text files of the 58 remaining records were then retrieved and read. Eleven of these studies, and a single study identified through the hand-search 20 (ie, a total of 12 studies), qualified for description in the review. Five of these studies 21 -25 met all the eligibility criteria and are included in data synthesis.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-text files of the 58 remaining records were then retrieved and read. Eleven of these studies, and a single study identified through the hand-search 20 (ie, a total of 12 studies), qualified for description in the review. Five of these studies 21 -25 met all the eligibility criteria and are included in data synthesis.…”
Section: Search Resultsmentioning
confidence: 99%
“…Allen 1998 26 Biofeedback included in both study arms Guarnieri 1990 29 Biofeedback included in both study arms Gerber 2008 27 One group received treatment not proven effective Gerber 2010 28 One group received treatment not proven effective Osterhaus 1993 30 Insuffi cient randomization Osterhaus 1994 31 Insuffi cient randomization Osterhaus 1997 20 Migraine not analyzed separately from tension-type headache The study reported no significant differences between completers and dropouts, but no information is given on how the dropouts were treated in the analyses, resulting in an unclear risk of bias for the study. In the study by Sartory et al, 23 16 children could not be contacted at follow-up.…”
Section: Table 1 Excluded Studies Studymentioning
confidence: 99%
“…However, five studies were later excluded because they did not meet the minimum criteria of 10 participants in each arm, therefore, leaving 29 studies. The third, which searched databases from 2008 to March 2012 yielded 851 abstracts, of which 25 papers were read in full, and eight further RCTs were included in the review, giving a total of 37 RCTs (Abram 2007; Alfven 2007; Barakat 2010; Barry 1997; Bussone 1998; Connelly 2006; Duarte 2006; Fichtel 2001; Gil 1997; Griffiths 1996; Hicks 2006; Humphreys 2000; Kashikar-Zuck 2005; Kashikar-Zuck 2012; Kroener-Herwig 2002; Labbe 1984; Labbe 1995; Larsson 1987a; Larsson 1987b; Larsson 1990; Larsson 1996; Levy 2010; Palermo 2009; McGrath 1988; McGrath 1992; Osterhaus 1997; Passchier 1990; Richter 1986;Robins 2005; Sanders 1994; Sartory 1998; Scharff 2002; Stinson 2010; Trautmann 2010; van Tilburg 2009; Vlieger 2007; Wicksell 2009). Nine further studies did not meet the inclusion criteria and were excluded (Fentress 1986; Kroener-Herwig 1998; Larsson 1986; Olness 1987;Sanders 1989; Trautmann 2008; Vlieger 2012; Weydert 2006; Youssef 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The first is best described as behavioural, typically relaxation based, with or without biofeedback, and including autogenic or hypnotherapeutic content (Bussone 1998; Fichtel 2001; Labbe 1984; Labbe 1995; Larsson 1987a; Larsson 1987b; Larsson 1990; Larsson 1996; McGrath 1988; McGrath 1992; Passchier 1990; Vlieger 2007). The second is best described as cognitive behavioural therapy, including cognitive coping, coping skills training, and parent operant strategies (Abram 2007; Alfven 2007; Barakat 2010; Barry 1997; Connelly 2006; Duarte 2006; Gil 1997; Griffiths 1996; Hicks 2006; Humphreys 2000; Kashikar-Zuck 2005; Kashikar-Zuck 2012; Kroener-Herwig 2002; Levy 2010; McGrath 1992; Osterhaus 1997; Palermo 2009; Richter 1986; Robins 2005; Sanders 1994; Sartory 1998; Scharff 2002; Stinson 2010; Trautmann 2010; van Tilburg 2009; Wicksell 2009). Different control conditions were employed that were categorised into either active control (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The main outcome measure, a composite pain index, was calculated on the basis of the reported pain intensity (VAS) multiplied by the frequency of pain (18). The scores ranged from 0 to 50.…”
Section: Pain Measuresmentioning
confidence: 99%